High-pressure homogenization as compared to pasteurization as a sustainable approach to obtain mandarin juices with improved bioaccessibility of carotenoids and flavonoids. (20th July 2020) - Sentandreu, Enrique; Stinco, Carla M.; Vicario, Isabel M.; Mapelli-Brahm, Paula; Navarro, José L.; Meléndez-Martínez, Antonio J.
Abstract: High-pressure technologies are among those with increased interest in the sustainable production of quality-enhanced food products. In this work, Ortanique mandarin juices have been submitted to traditional pasteurization conditions (time/temperature of 65 °C/15 s, 85 °C/15 s and 92 °C/30 s) and energy-saving high-pressure homogenization (HPH, 150 MPa) treatments to compare the effects on the physicochemical composition and in vitro bioaccessibility of carotenoids and flavonoids. In general, physicochemical attributes of the homogenized sample were similar to those found in fresh juice, with similar ascorbic acid content and cloudiness but with significant colour differences in all cases. The bioaccessibility of total carotenoids was similar in fresh and pasteurized juices in contrast to the HPH sample that exhibited a five-fold increase, which suggests a positive effect of particle size reduction to favour the action of digestive enzymes. A clear increase in the levels of epoxycarotenoids was detected in the micellar fractions of digested HPH juices, although such carotenoids are not detected in human fluids or tissues. Regarding the bioaccessibility of flavonoids, no significant differences were found in the samples studied. Results obtained can help the implementation of HPH processing to obtain natural beverages with enhanced nutritional properties. Graphical abstract: Image 1 Highlights: Bioaccessibility of carotenoids and phenolics from mandarin juices was studied. Pasteurization and energy-saving high-pressure homogenization (HPH) were compared. Five-fold increases in total carotenoids bioaccessibility by HPH processing observed. Overall, bioaccessibility of flavonoids remained unchanged by both treatments. HPH is a sustainable option to obtain juices with improved nutritional properties.